Undiagnosed tuberculosis associated with hemophagocytic lymphohistiocytosis due to improper use of corticosteroid - Hadi Allahverdi Nazhand; Shahram Sabeti; Farid Javandoust Gharehbagh; Ronak Nalini; Abdolreza Babamahmoodi; Maryam Marahemi; Elmira Mahmoudi Chalmiani; Legha Lotfollahi; Ilad Alavi Darazam (Journal of Infection in Developing Countries)
Introduction: Hemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening hematologic disease segregated into familial (primary) and acquired (secondary) subtypes. Hyperinflammation and HLH occur when the immune system fails to clear activated macrophages and histiocytes. Infections, malignancies, and rheumatologic disorders are the major triggers leading to HLH. Miliary tuberculosis is a serious disease with a lymphohematogenous spread of Mycobacterium tuberculosis, which is known to be one of the causative agents of HLH. Miliary tuberculosis and HLH have atypical presentations which are similar to routine diseases. Hence, physicians may face challenges to diagnose and treat these complications.